Multimedia Based VCT for Islamic Character Awareness: Pengembangan VCT Berbasis Multimedia untuk Kesadaran Karakter Islami - Izmi Lutfiah; Mardianto Mardianto; Mahariah Mahariah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Islamic Religious Education requires learning approaches that support not only cognitive attainment but also the affective domain and character formation. Specific Background: At SMP Muhammadiyah 56 Binjai, Grade VII Islamic Religious Education learning was still largely teacher centered, theoretical, and minimally dialogic, so students had limited opportunities to reflect on and internalize Islamic values in daily life. Knowledge Gap: Existing learning practices had not optimally facilitated value clarification, moral reflection, and conscious decision making, while students’ Islamic character awareness remained low. Aims: This study aimed to develop a multimedia based Value Clarification Technique model for Islamic Religious Education and examine its feasibility, practicality, and outcomes in fostering students’ Islamic character awareness. Results: Using Research and Development with the ADDIE model, the study involved 18 Grade VII students, an Islamic Religious Education teacher, and school stakeholders. The developed product obtained very high material validity (98%) and design validity (97%), while practicality reached an average of 95.2%. Learning outcomes also improved, with the mean score increasing from 54 on the pretest to 80 on the posttest, an N-Gain of 0.534 in the moderate category, and mastery rising from 11% to 83%. Novelty: The study offers an integrative Value Clarification Technique model supported by interactive video and reflective value discussion specifically designed for Islamic Religious Education. Implications: This model provides a structured and contextual alternative for strengthening Islamic character awareness and the affective dimension of learning in junior secondary Islamic Religious Education. Highlights• Developed a multimedia-supported Value Clarification Technique model through the ADDIE stages for Grade VII Islamic Religious Education.• Achieved very high feasibility and usability, with 98% material validity, 97% design validity, and 95.2% practicality.• Recorded learning progress from a mean pretest score of 54 to 80, with N-Gain 0.534 and mastery rising from 11% to 83%. KeywordsValue Clarification Technique; Islamic Religious Education; Islamic Character Awareness; Multimedia Learning; Affective Domain